On-farm evaluation of introduced maize varieties and their yield determining factors in East Timor - Williams, R.; Borges, L.; Lacoste, Myrtille; Andersen, R.; Nesbitt, H.; Johansen, C. (Elsvier, 2012)
Maize is the major food crop of East Timor. It is grown under subsistence farming and its yields are low (1.0-1.7tha -1 ), with production insufficient to meet national needs. The " Seeds of Life" project, operating since 2001, has introduced open-pollinated maize varieties from other countries via the International Maize and Wheat Improvement Center (CIMMYT) and evaluated them for their suitability in local farming systems. Firstly, introductions were screened for yield potential and farmer-acceptable traits in replicated trials on research stations. Then, best selections were provided to farmers for evaluation against their local varieties under their own cultivation practices. More than 1000 on-farm trials were conducted across all of the agro-ecological zones of East Timor from the 2005/06 to the 2008/09 season. Mean annual yield advantage of the test varieties Suwan 5 and Sele over " local" varieties ranged from 36 to 54% and considerable initial adoption and diffusion to non-participating households was recorded. The large number of trials conducted over a wide range of agro-ecological and management conditions provided the opportunity to use analysis of variance to test the significance of factors contributing to yield. Major yield determinants were variety, agro-ecological zone, soil pH, plant density at harvest, frequency of project staff visits and wealth status of farmer. This combination of varietal testing with agronomic assessment has provided a basis for refinement of recommended cultivation practices for maize in East Timor. The project has demonstrated the feasibility of raising national maize production so as to approach national consumption needs. However, major constraints to realizing this potential are production of quality seed of improved varieties and its widespread distribution and effective extension of improved cultivation and grain storage practices. © 2012 Elsevier B.V.